2019
DOI: 10.1007/s10682-019-09977-0
|View full text |Cite
|
Sign up to set email alerts
|

Predation decreases cohort foraging activity and growth, yet increases individual size variation in prey

Abstract: There is increasing evidence that size variability within a cohort can have important consequences on community ecology and evolution. It is commonly assumed that the threat of predation can influence cohort size variability by homogenizing foraging behavior among members. We combined predictions of growth-defense models with those from models of genesis of size variation to test the non-lethal effects of size-selective newt and gapeunconstrained aeshnid dragonfly larva predators on the size structure of Rhaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Under this scenario, the sensory receptors used to detect the predation stimuli become fatigued and lose their sensitivity as the frequency of exposure to the stimuli increases (Ferrari et al, ). However, habituation may not be the main mechanism operating here because an earlier study (Ramamonjisoa, Oiire, Zheng, & Kimura,) suggested that the tadpoles of R. arboreus can exhibit high level of defense over long exposure to high predation risk. A related hypothesis suggests that prey that are chronically exposed to high background level of risk can initially display high intensity of antipredator response, but gradually decrease responsiveness and increase foraging rates because long bouts of vigilance cannot be sustained while meeting energy needed for growth (Ferrari, Sih, & Chivers, ; Ferrari et al, ).…”
Section: Discussionmentioning
confidence: 89%
“…Under this scenario, the sensory receptors used to detect the predation stimuli become fatigued and lose their sensitivity as the frequency of exposure to the stimuli increases (Ferrari et al, ). However, habituation may not be the main mechanism operating here because an earlier study (Ramamonjisoa, Oiire, Zheng, & Kimura,) suggested that the tadpoles of R. arboreus can exhibit high level of defense over long exposure to high predation risk. A related hypothesis suggests that prey that are chronically exposed to high background level of risk can initially display high intensity of antipredator response, but gradually decrease responsiveness and increase foraging rates because long bouts of vigilance cannot be sustained while meeting energy needed for growth (Ferrari, Sih, & Chivers, ; Ferrari et al, ).…”
Section: Discussionmentioning
confidence: 89%
“…It is unclear why stickleback might cause bigger differences among individuals at low content of astaxanthin expression (i.e., when predation risk is presumably the highest). One possibility is that non‐linear responses relating astaxanthin content to predation risk (or to UVR risk) generate a wider variation at high predation risk (Ramamonjisoa et al, 2019 ), but to test this we would need to rear copepods from multiple populations in common garden environments and measure astaxanthin reaction norms in response to variation in fish cues and UVR stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results aligned with previous research on Common Toad tadpoles, similarly reared in a common garden environment, which were shown to decrease their activity levels (which can correlate with boldness; Kelleher et al 2018 ) across larval development (Kurali et al 2018 ). Thus, it is likely that tadpoles early in development (after the consumption of the yolk sac; Gosner 1960 ) show increased foraging activity and boldness to enhance resource acquisition, which then lessen over time due to consequent growth and energy storage (Ramamonjisoa et al 2019 ; Davenport et al 2020 ). This change in behavioral traits across ontogeny, potentially related to energetics, will also play an important role in interpreting future research on how traits, like boldness, change between life stages and how this may or may not relate to adaptive behavioral shifts associated with urbanization or biological invasions.…”
Section: Discussionmentioning
confidence: 99%